ANALYSIS OF PUBLIC PREFERENCES FOR ZAKAT PAYMENTS COMPARED TO TAXES IN A SOCIAL AND ECONOMIC PERSPECTIVE - Lubis, Muhammad Arifin; Husna, Asmaul (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to analyze public preferences in choosing zakat over taxpayments from social and economic perspectives. Using a qualitative approachand literature study method, the research examines prior studies, accreditedjournals, and relevant policy documents related to zakat and taxation. Thefindings indicate that public preference for zakat is influenced by religiousmotivation, higher trust in zakat management institutions, ease of access throughdigital platforms, and social-cultural satisfaction. In contrast, low trust in taxauthorities, negative perceptions of bureaucracy, and lack of transparency arekey factors behind weak tax compliance. These findings suggest the need for anintegrative policy approach that aligns zakat and taxation to enhance fiscaljustice and effective wealth distribution in society. The study recommends thatgovernments and zakat institutions strengthen collaboration, improvetransparency, and develop regulations that accommodate the social and religiousvalues of the public.